Yields of mesenchymal stromal cells from synovial fluid reflect those from synovium in patients with rheumatoid arthritis. (April 2022) - Kohno, Yuji; Mizuno, Mitsuru; Endo, Kentaro; Ozeki, Nobutake; Katano, Hisako; Matsumoto, Mikio; Kaneko, Haruka; Takazawa, Yuji; Koga, Hideyuki; Sekiya, Ichiro
Graphical abstract: Highlights: Primary MSC yields were correlated for synovial fluid and synovium of RA knees. Synovial fluid MSC yield predicted MSC yield from the synovium of an RA patient. Chondrogenic potential was lower in synovial fluid MSCs than in synovial MSCs. Synovial fluid MSC chondrogenic potential did not predict synovial MSC potential. Abstract: The yield of primary synovial mesenchymal stromal cells (MSCs) from synovium of patients with rheumatoid arthritis (RA) is highly variable, but cell transplantation therapy with autologous synovial MSCs requires accurate prediction of the synovial MSC yield per synovium weight. Here, we determined whether the yield of synovial fluid MSCs might predict the ultimate yield of primary MSCs from the synovium of RA knees. Synovial fluid and synovium were harvested during total knee arthroplasty from the knee joints of 10 patients with RA. Synovial fluid (1.5 mL) was diluted fourfold and plated equally into six 60 cm 2 dishes. Nucleated cells from digested synovium were similarly plated at 1 × 10 4 cells in 6 dishes. All dishes were cultured for 14 days and analyzed for MSC yields and properties, including in vitro chondrogenesis. The cultured synovial cell number was correlated with the cultured synovial fluid cell number (n = 10, R 2 = 0.64, p < 0.01). Synovial fluid cells formed cell colonies and showed MSC-like surface epitopes and multi-differentiation potential. However, the cartilage pellet weight indicated a greater chondrogenic potential of the synovial MSCs (n = 8). The primary MSC yields from synovial fluid and synovium were correlated, indicating that the synovial fluid MSC yield can predict the ultimate synovial MSC yield.